1989
DOI: 10.1136/gut.30.5.573
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gastric body and antral pH: a 24 hour ambulatory study in healthy volunteers.

Abstract: SUMMARY Simultaneous ambulatory records of gastric antral and body pH were made over 24 hours in nine healthy volunteers by means of endoscopically positioned and anchored glass electrodes. Intragastric pH was temporarily raised after the endoscopy with the median pH value 30 minutes after the procedure being 3.9 (range 1 5-70) for the antrum and 4.1 (range 1 5-70) for the body. Daytime pH (median pH value between 1200 h and 2300 h) was lower in the antrum (median=1.9, range 16-2.6) than in the body (median=2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 14 publications
5
62
1
1
Order By: Relevance
“…Parietal cells also secrete concentrated HCl, which presumably results in more frequent exposure to acid in the corpus. The pH of the corpus, however, is not lower overall than that of the antrum, although it does display a broader range (8,32,51). Thus, the different regions of the stomach possess distinct physiological characteristics that likely present H. pylori with different chemotactic signals.…”
Section: Discussionmentioning
confidence: 97%
“…Parietal cells also secrete concentrated HCl, which presumably results in more frequent exposure to acid in the corpus. The pH of the corpus, however, is not lower overall than that of the antrum, although it does display a broader range (8,32,51). Thus, the different regions of the stomach possess distinct physiological characteristics that likely present H. pylori with different chemotactic signals.…”
Section: Discussionmentioning
confidence: 97%
“…McLauchlan and colleagues (69) reported that pH dynamics after a meal can be more pronounced in the stomach corpus than in the antrum, providing a more challenging environment for H. pylori to colonize persistently (10,11,15). On the other hand, the antrum might provide more inflammation and produce more reactive oxygen than the corpus (25), in particular during late infection.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the slight alkalinity of the fasting python's stomach, mammals maintain a highly acidic environment (pH 1.1-3) within their stomachs between bouts of digestion (Youngberg et al, 1985;Evans et al, 1988;Cilluffo et al, 1990;Viani et al, 2002). Whereas pythons experience a dramatic postprandial decrease in gastric pH, the luminal pH of mammal stomachs increases rapidly after feeding to range between 3 and 6, presumably as the ingested meal buffers the gastric acid (Savarino et al, 1988;McLauchlan et al, 1989;Cilluffo et al, 1990). Within a few hours after feeding, intragastric pH of mammals drops as acid production, which has increased 20-fold, overwhelms the buffering capacity of the food, which is then being passed through the pyloric sphincter into the small intestine (Fordtran and Walsh, 1973).…”
Section: Gastric Phmentioning
confidence: 99%